Effective Sentence Writing in Story Problems on the Arithmetic Operations of Whole Numbers in Grade IV of State Elementary School Pelandakan 1 - Jannah, Widia Nur; Herman, Tatang; Agustin, Mubiar; Damaianti, Vismaia S.; Mamat, Nordin Bin (Mimbar Sekolah Dasar, 2024)
This study aims to evaluate the advantages and disadvantages of using effective sentences in writing story problems related to integer arithmetic operations. The research methodology used is descriptive analysis with a qualitative approach, and case study design to explore in depth a phenomenon or problem. Data were collected through a documentary study of story problems used in resources for arithmetic procedures involving integers. Furthermore, interviews were conducted with teachers to find out their perspectives on the formulation of the problems. The data analysis technique was carried out by categorizing sentences in narrative story problems and assessing their effectiveness based on linguistic criteria and clarity of information. The results of the study showed that most of the narrative story problems analyzed did not fully meet the criteria for effective sentences. There were vague, long, and imprecise sentences so that they did not convey the information needed. Certain questions also contained terminology that was less familiar to students. This study identified the need for improvements in sentence structure and vocabulary selection to be more appropriate to students' level of understanding. This study shows the need for teacher training in composing effective sentences for story problems in order to improve the quality of questions presented to students.